Enhanced Photocatalytic Degradation of Tetracycline-Class Pollutants in Water Using a Dendritic Mesoporous Silica Nanocomposite Modified with UiO-66 - Deymeh, F.; Ahmadpour, A.; Allahresani, A.; Arami-Niya, Arash (2023)
Tetracyclines (TTCs), a widely used group of antibiotics in agriculture and animal husbandry, cause water pollution and the emergence of antibiotic-resistance genes. This study reports the synthesis of a metal-organic framework nanocomposite of UiO-66 based on modified dendritic fibrous nanosilica to act as a photocatalyst for the degradation of doxycycline (DOX) and TTC as drug model pollutants in water. This nanocomposite demonstrated about three times better photodegradation performance than UiO-66 due to a decreased electron-hole recombination rate, increased conductivity, and decreased band gap, leading to the higher pollutant reduction efficiency. Structural and morphological analyses were performed on the nanocomposite, and various influencing parameters, including sample pH, catalyst dose, and irradiation time, were studied on the photocatalytic degradation of DOX and TTC to optimize the photodegradation process. At the optimum condition, the maximum photodegradation of 97.2 ± 3.1% was achieved for solutions containing 200 mg·L-1 each drug. The results showed that the proposed photocatalyst is stable and effective in eliminating TTC-class pollutants from water and wastewater with high efficiency and fast kinetics. The reusability of the catalyst was examined, and no significant decrease in the efficiency of the catalyst was observed after five times.